2019
DOI: 10.1248/yakushi.19-00122
|View full text |Cite
|
Sign up to set email alerts
|

The Adverse Effects of Ephedra Herb and the Safety of Ephedrine Alkaloids-free Ephedra Herb Extract (EFE)

Abstract: a 北里大学東洋医学総合研究所(〒108 8642 東京都港区白金 5 9 1), b 北里大学薬学部(〒108 8642 東京都港区白金 5 9 1), c 東京理科大学薬学部(〒278 8510 千葉県野田市山崎 2641) , d 株式会社常磐植物化学研究所(〒285 0801 千葉県 佐倉市木野子 158 番地) , e 松山大学薬学部(〒790 8578 愛媛県松山市文京町 4 2) , f 国立医薬品食品衛生研究所(〒210 9501 川崎市川崎区殿町 3 25 26) 現所属: † 東邦大学薬学部(〒274 8510 千葉県船橋市三山 2 2 1)  e-mail: hyuga-s@insti.kitasato-u.ac.jp

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…Kampo formulas consist of various combinations of crude drugs, traditionally regarded as units, and are often used on the base of ancient experience ( Tanaka et al, 1995 ; Odaguchi et al, 2019 ). In Japan, Kampo formulas are covered by the national health insurance system and are prescribed by doctors under the condition of government subsidies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kampo formulas consist of various combinations of crude drugs, traditionally regarded as units, and are often used on the base of ancient experience ( Tanaka et al, 1995 ; Odaguchi et al, 2019 ). In Japan, Kampo formulas are covered by the national health insurance system and are prescribed by doctors under the condition of government subsidies.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the combination of Ephedrae herba with other crude drugs in Kampo formulas has a weaker antiviral effect than that of Ephedrae herba. Ephedra herba has various side effects, and Kampo formulas are shown to contain crude drugs that alleviate the side effects of the strong Ephedra herba ( Odaguchi et al, 2019 ). The reduced suppressive effect of Ephedra herba on virus infection may mean that its side effects on the human body are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of Chinese herbal medicines is often queried. Aristolochia fangchi ( Tankeu et al, 2016 ) and Ephedra ( Odaguchi et al, 2019 ) are reported with a number of serious adverse effects on the cardiovascular and nervous system. The herbs of Yuanjiang decoction used in this study have been standard for decades.…”
Section: Discussionmentioning
confidence: 99%
“…One study found 33% of products tested contained unlisted ingredients (Newmaster et al., 2013 ), whilst a 2019 study reported that 27% of the herbal products in the global marketplace were adulterated (Ichim, 2019 ). Many commercially available herbal remedies also have toxic effects when used in larger doses, or in certain circumstances (Chen et al., 2013 ; Cohen & Ernst, 2010 ; De Groot, 2013 ; Ernst, 2000 ; Fu et al., 2008 ; Lee et al., 2020 ; Lynch et al., 2006 ; McEwen, 2015 ; Mei et al., 2017 ; Nazari et al., 2017 ; Odaguchi et al., 2019 ; The Alpha‐Tocopherol Beta Carotene Cancer Prevention Study Group, 1994 ; Venkatramani et al., 2013 ; Werneke et al., 2004 ). Herbal products are usually controlled under different regulations to drugs (e.g., as dietary supplements or natural health products) and have not been subjected to the same scientific scrutiny.…”
Section: Discussionmentioning
confidence: 99%